2021
DOI: 10.1002/ldr.4033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of altitude, aspect, and soil depth on carbon stocks and properties of soils in a tea plantation in the humid Black Sea region

Abstract: Physiographic factors effectively alter soil properties and carbon storage. However, previous research on the effect of topographic factors affecting soil properties on carbon stocks in tea plantations has been limited in the humid Black Sea region. The aim of this study was to determine the effects of elevation, aspect, and soil depth on carbon stocks and soil properties of tea plantations in the Black Sea region. The tea plantations in the research area were divided into two elevation steps and two different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 57 publications
0
7
2
Order By: Relevance
“…The clay content in tea fields increased with the increase in elevation at both soil depths. In contrast to our results, a study conducted by Yuksek et al [26] in the same region determined that the clay content of soils decreased with increasing elevation in tea fields. This difference might be due to the differences in the parent material, land use history, and soil texture properties.…”
Section: Clay (%)contrasting
confidence: 99%
See 2 more Smart Citations
“…The clay content in tea fields increased with the increase in elevation at both soil depths. In contrast to our results, a study conducted by Yuksek et al [26] in the same region determined that the clay content of soils decreased with increasing elevation in tea fields. This difference might be due to the differences in the parent material, land use history, and soil texture properties.…”
Section: Clay (%)contrasting
confidence: 99%
“…Sand content in the tea fields decreased at both depths with the increase in elevation. This result is in contrast with Yuksek et al's [26] findings in a neighboring city, Rize. They reported that the sand content of the soils increased in the tea areas with the increase in elevation.…”
Section: Clay (%)contrasting
confidence: 95%
See 1 more Smart Citation
“…There are many factors that effects the soil physicochemical properties like elevation, parent material or geological formation, human activities or interferences and climatic characteristics [83]. In these study the prime factors affecting the soil properties are parent material, heavy rainfall, weathering processes, high aluminum (Al), iron and manganese contents [21] and the large number of base cations leaching from soil [57].…”
Section: Effects Of Tea Plantation On Selected Physicochemical Proper...mentioning
confidence: 99%
“…Only a few studies have specifically examined and evaluated SOC and N stock within the context of tea plantations. Some studies have explored the impact of converting forests into tea plantations (e.g., Chen et al 2016 ; Chiti et al 2018 ; Sohng et al 2017 ; Yüksek and Yüksek 2021 ; Yulnafatmawita et al 2020 ). The reversion of tea plantations to forests or the implementation of different management practices has rarely been investigated in literature.…”
Section: Introductionmentioning
confidence: 99%